Aktualisasi Manajemen Pendidikan dan Dakwah Bi Al-Hal Melalui Media Voucher Infaq dalam Menunjang Kemakmuran Masjid Nurus Saadah Kota Salatiga - Sri Rokhmiyati (UMSU, 2021)
Management is one of the most important aspects in managing a dynamic and diverse society, so it can be solved by good management in the community. Da'wah with its various variations always fills the joints of the life of every religious community. Of course, it cannot be separated from the elements of Islamic education management in society. This study aims to describe the actualization of education management and instill the values of da'wah bil hal through an infaq voucher program that is tailored to the needs of the local community. Da'wah bi al-hal through Participatory Action Research can actually bring benefits and change for the community in realizing their hopes and finding solutions to their difficulties. This activity involved stakeholders Blotongan Village, religious and community leaders, mosque takmir and mosque youth. The results of the study show that the application of education management and da'wah bil things that have been done can increase participation, environmental awareness, and through the media infaq vouchers are able to support the prosperity of the mosque.